Aplikasi pewarna tekstil alami Morinda citrifolia dengan mordan Averrhoa bilimbi (Molimbi-dye) untuk jenis kain katun, nylon, dan polyester - Ghauts Mannah Aji Abdillah; Rizal Muhaimin; Viska Rinata; Devi Mariya Sulfa; Indra Kurniawan Saputra (AGROINTEK, 2024)
One of the ingredients for making synthetic textile dyes is azo and acrylic which are carcinogenic, causing bladder and kidney cancer. There is a solution to replace synthetic textile dyes of Nusa Tenggara region by using natural dyes from Morinda citrifolia root. This has been done for generations, but it’s only applied to cotton fabric. Basically, natural dyes have low color fastness. Therefore, it’s mixed with Averrhoa bilimbi extract which contains a mordant substance to strengthen the color fabric. The purpose of study are to find out the best composition for making Molimbi-dye, the effectiveness of Molimbi-dye application on the three types of fabrics, and to find out Molimbi-dye as a natural textile dye that can replace synthetic textile dyes. The calculation of the composition of Molimbi-dye are 0.5 g/ml, 1.0 g/ml, and 1.5 g/ml from the ratio of the composition to kitchen ash water in a fixed volume of 500 ml. The effectiveness of the Molimbi-dye application is calculated using the RGB (Red, Green, Blue) decimal code which is calculated using RGB calculator to get the average RGB calculation result. Data are analyzed using Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) post hoc, with a significance level of α0.05. The results showed that Molimbi-dye staining of cotton, nylon and polyester, produced the colors hopbush, cotton candy, and mauvelous using the best composition, density 1.5 g/ml. Meanwhile, the result of synthetic textile dyes staining of cotton, nylon and polyester, produced the colors royal health, melanie and pale violet. The results of these two dyes are very similar on cotton and polyester fabrics, but on nylon fabrics, Molimbi-dye is seen to be more easily absorbed by fabrics than synthetic textile dyes. In this way, Molimbi-dye can be said to be superior, so it can replace synthetic textile dyes.